2019
DOI: 10.1037/pas0000718
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of signal- and event-contingent ambulatory assessment of interpersonal behavior and affect in social situations.

Abstract: Ambulatory assessment (e.g., ecological momentary assessment) is now widely used in psychological research, yet key design decisions remain largely informed by methodological lore as opposed to systematic inquiry. The present study experimentally tested whether signal-(e.g., random prompt) and event-(e.g., complete a survey every time a target event occurs) contingent recording procedures of interpersonal behavior and affect in social situations yield equivalent quality and quantity of data. Participants (N ϭ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 30 publications
1
58
0
Order By: Relevance
“…Many researchers are already making great strides in increasing reproducibility and transparency in the field of ESM research (e.g. Dejonckheere et al, 2018;Heininga et al, 2019, Himmelstein et al, 2019van Roekel et al, 2019;Zhang et al, 2018) and in clinical psychology more broadly (Tackett et al, 2017;Tackett et al, 2019), where much ESM research is conducted. The adoption of open science practices in ESM research is, however, still in its elementary stages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers are already making great strides in increasing reproducibility and transparency in the field of ESM research (e.g. Dejonckheere et al, 2018;Heininga et al, 2019, Himmelstein et al, 2019van Roekel et al, 2019;Zhang et al, 2018) and in clinical psychology more broadly (Tackett et al, 2017;Tackett et al, 2019), where much ESM research is conducted. The adoption of open science practices in ESM research is, however, still in its elementary stages.…”
Section: Discussionmentioning
confidence: 99%
“…Open science practices, including pre-registration of hypotheses and analysis plans on the Open Science Framework prior to data collection and/or analysis (Nosek, Ebersole, DeHaven, & Mellor, 2018), are initiatives that aim to promote scientific transparency, reproducibility, and replicability. Whilst off to a promising start, the implementation of open science approaches to ESM research, including pre-registration, preprinting and sharing of code and/or materials, are only just emerging (e.g., Dejonckheere, Kalokerinos, Bastian, & Kuppens, 2018;Heininga et al, 2019;Himmelstein et al, 2019;van Roekel et al, 2019;Zhang, Smolders, Lakens & Ijsselsteijn, 2018), and there is still some way to go before such practices become widely adopted.…”
Section: Esm Research and Open Science Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, huge differences exist in how state measures have been developed. With few exceptions (Bleidorn, 2009;Himmelstein et al, 2019;Moskowitz, 1994;Newman, Sachs, Stone, & Schwarz, 2019;Ostojic-Aitkens, Brooker, & Miller, 2019;Zimmermann et al, 2019, Study 2), the state measures were not tested and validated in an independent sample, before the data collection of the substantive study. The most common way to developing state measures thus far seems to be to take items or adjectives that were used to assess personality traits and transform them into state measures (e.g., Horstmann, Rauthmann, Sherman, & Ziegler, in revision;Ziegler, Schroeter, Lüdtke, & Roemer, 2018).…”
Section: Current Practicesmentioning
confidence: 99%
“…A systematic review of diet and physical activity in youth reported response latency longer than 15 min in 0 to 40% of studies using electronic devices, compared to 71.7 to 74.1% for paper-and-pencil methods [42]. A study reported an average response latency of 29 min [45], and another reported 19 min [46]. The participants of those studies were youth (e.g., high school or undergraduate students) who probably responded faster to an EMA than our participants.…”
Section: Limitationsmentioning
confidence: 99%